How to make an accurate diagnosis of fetal pyriform sinus fistula in utero: experience at a single medical center in mainland China. (September 2018) - Liu, Zequn; Han, Jin; Fu, Fang; Liu, H.S; He, Qiu-ming; Zhong, Wei; Wang, Hongying; Yang, Xin; Li, Dongzhi; Liao, Can
Abstract: Objective: The aim of this study was to make an accurate diagnosis of pyriform sinus fistula (PSF) for prenatal diagnosis. Study design: Medical records were reviewed for all 35 pyriform sinus fistula patients presenting between 2011 and 2017. Ultrasonography (US), fetal magnetic resonance imaging (MRI) and karyotyping were offered during gestation, while computer tomography (CT) and barium esophagography were performed after birth. Results: Patients included 21 males (60%) and 14 females (40%) with a sex ratio of 1.5:1. The lesion was located on the left side in 32 (91.4%) cases, the right side in 2 (5.7%), and was bilateral (2.8%) in only one case. The sensitivity of CT, MRI, ultrasonography and barium esophagography were 100% (35/35), 69.2% (9/13), 22.9% (8/35), and 80% (20/25), respectively. If the diagnosis was correct, there was almost no recurrence after treatment. Karyotype analysis of all fetuses was normal. Conclusions: Pyriform sinus fistula is more commonly seen in the left side. Compared with ultrasonography, MRI has more advantages in prenatal diagnosis, and it is more accurate in postpartum CT examination. The outcome of children with pyriform sinus fistula may be guarded when it correct diagnosis.